Meningkatkan Perilaku Menabung UMKM Cikupa dengan Implementasi Strategi Financial Nudging yang Efektif - Munir Nur Komarudin; Dadang Suhardi; Deri Prayudi; Darul Fadli; Dzalika Bunga Azzahra (Universitas Insan Cendekia Mandiri, 2026)
This community service activity aims to test the effectiveness of the implementation of the Financial Nudging strategy in improving savings behavior among Micro, Small, and Medium Enterprises (MSMEs) in Cikupa Village, Darma Kuningan. The local MSME community often faces challenges of undisciplined cash management and high financial vulnerability, which are key issues relevant to the sustainability of their businesses. The method used is a behavior-based intervention with a direct survey approach, involving a series of subtle